2016
DOI: 10.1161/atvbaha.115.306607
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Hyaluronan Synthase 3 Inhibits Neointimal Hyperplasia in Mice

Abstract: Objective Hyaluronan (HA) is a polymeric glucosaminoglycan that forms a provisional extracellular matrix in diseased vessels. HA is synthesized by three different HA-synthases (HAS1, -2, -3). Aim of this study was to unravel the role of the HAS3 isoenzyme during experimental neointimal hyperplasia. Approach and Results Neointimal hyperplasia was induced in Has3-deficient mice by ligation of the carotid artery. HA in the media of Has3-deficient mice was decreased 28 days after ligation and neointimal hyperpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…On the one hand, the current data are in line with a local effect of macrophage-released IL-1β on HAS3 expression in vascular SMC. In the light of the previous results that HAS3 promotes neointimal hyperplasia in vivo and migration and proliferation of SMC in vitro [12] it is likely that IL-1β thereby also promotes SMC dependent aspects of atheroprogression because HAS3 will create an HA- rich microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, the current data are in line with a local effect of macrophage-released IL-1β on HAS3 expression in vascular SMC. In the light of the previous results that HAS3 promotes neointimal hyperplasia in vivo and migration and proliferation of SMC in vitro [12] it is likely that IL-1β thereby also promotes SMC dependent aspects of atheroprogression because HAS3 will create an HA- rich microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Has3 -deficient mice were generated by genOway (Lyon Cedex, France) as described by Kiene et al [12] and then crossbred with Apoe -deficient mice (Taconic; Hudson, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Kiene et al reported an important role for hyaluronic acid synthase (HAS)-3 during neointimal formation in mice. 62 When examined 28d after carotid ligation injury in HAS3-deficient mice, HA content of the artery wall was greatly reduced and formation of a neointima was strongly inhibited compared to wild type animals. 62 Transcriptome analysis in HAS3-deficient carotid arteries suggested that genes involved in cell migration including focal adhesion proteins, SMC integrins, and PDGF-BB signal pathway mediators were downregulated.…”
Section: Vascular Smcs and Adaptive Wall Remodelingmentioning
confidence: 99%
“…62 When examined 28d after carotid ligation injury in HAS3-deficient mice, HA content of the artery wall was greatly reduced and formation of a neointima was strongly inhibited compared to wild type animals. 62 Transcriptome analysis in HAS3-deficient carotid arteries suggested that genes involved in cell migration including focal adhesion proteins, SMC integrins, and PDGF-BB signal pathway mediators were downregulated. The authors conclude that HAS3-mediated hyaluronan production supports important steps in SMC migration and neointimal formation in vivo .…”
Section: Vascular Smcs and Adaptive Wall Remodelingmentioning
confidence: 99%